William Logan's 1850 History of the Geological Survey of Canada - Smith, Charles (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1999)
Summary William Logan wrote the first history of the Geological Survey of (the Province) of Canada in 1850. It was published, anonymously, in a non-geological venue, Scobie's Canadian Almanac for the year 1851. Because of its publication venue, the "history" seems unknown to geological literature. In the history Lo-gan presented a public case for the economic value of geological surveys, to a political, commercial and public audience in Canada, while not appearing to meddle in the political process of theday. Included was a "Catalogue of Economic Minerals of Canada" bearing Logan's name, and which he used to plan the successful Canadian contribution to the 1851 Industry Exhibition, held in London. The history and the Catalogue texts, and their uses, show that Logan was a master in generating public awareness of the benefits of geological surveys in Canada, and of the economic potential of Canada's mineral resources abroad.